An alternative to align interactive interfaces construction and return channel usage - Lima, Giuseppe; Batista, Claudiana; Oliveira, Felipe; Barros, Ighor; Fernandes, Marcelo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
It is recommendable that Interactive Digital TV application development should be oriented by user interface structure and interaction design. Better interactivity experiences can be obtained with the return channel usage, contributing to the offering of more convergent applications and addressing their integration to remote businesses logics and services. Many solutions enable construction of interactive applications with textual/visual programming support, but a few of them considers the disposal between the services operated over a return channel, the underlying data and the application widgets. Usually, these solutions require the direct manipulation of intermediary models whose their structures and notations demand an additional learning effort and, in some cases, they only focus on the achievement of a specific domain application template, instead of the final application instance itself. An alternative for application authoring will be presented aiming to abstract both the visual programming interface structure domain and its behavior/responsiveness when it requires the usage of the return channel based on services over IP and meeting the expectances for agility and quality in digital interactive television conception.